Preparation of Fe3O4/SiO2/TiO2/PrVO4 nanocomposite in various molar ratios: Investigation on photocatalytic performance on organic contaminate and bacterial environments, and anti-cancer properties. (15th January 2020) - Amin Marsooli, Mohammad; Rahimi Nasrabadi, Mahdi; Fasihi-Ramandi, Mahdi; Adib, Kourosh; Eghbali, Mohammad; Pourmasoud, Saeid; Ahmadi, Farhad; Sohouli, Esmail; Sobhani Nasab, Ali; Ali Mirhosseini, Seyed; Reza Ganjali, Mohammad
Graphical abstract: Highlights: Fe3 O4 /SiO2 /TiO2 /PrVO4 were synthesized using new method in various molar ratios. The photocatalytic properties of nanocomposites were investigated under visible light. The photo-antibacterial effect of nanocomposite on various bacteria was evaluated. The anti-cancer properties of Fe3 O4 /SiO2 /TiO2 /PrVO4 for panc1 cells were evaluated. Abstract: Various SiO2 /TiO2 nanoparticles coated on Fe3 O4 core and a nanocomposite with PrVO4 were prepared through an ultrasonic-assisted co-precipitation approach. The sample with optimal properties for the photocatalytic degradation of rhodamine-B under visible light (around 55% for degradation in 100 min) was chosen, and its photo-antibacterial effects against gam-positive and negative Staphylococcus aureus (ATCC 6538) and Escherichia coli (ATCC 25922) under UV–Vis light was evaluated. Also, the cytotoxicity properties on Panc1 cells using the MTT assay studied and its IC50 is about 250 mg/L. Structural, morphological and magnetic characteristics of the nanocomposites were evaluated through XRD, FT-IR, SEM, EDX, MAP, UV–Vis DRS, and VSM tests. The crystalline size of Fe3 O4 /SiO2 /TiO2 nanoparticles and Fe3 O4 /SiO2 /TiO2 /PrVO4 were determined to be in the range of 55–75 nm, and 80–100 nm respectively, through SEM tests. XRD results indicated that the nanocomposites were pure and VSM analyses proved that the saturation magnetization of the sample is adequate for its applications.